Sosialisasi Isu-Isu Kebaharuan Akuntansi Syariah - Rufaida, Erty Rospyana; Asnidar, Asnidar (Abdurrauf Journal of Community Service, 2024)
Islam teaches comprehensive and holistic principles that cover all aspects of human life, including in the economic field. One important aspect of Islamic economics is Islamic accounting, which aims to integrate Islamic principles into the modern accounting system to create a fairer and more dignified system. With the rapid growth of the financial market and the increasingly urgent need for financial literacy, understanding Islamic accounting is crucial. This study identified that Islamic financial literacy in the Riau community, especially in Pekanbaru City and Kuantan Singingi, is still low, so education about Islamic finance is very much needed. This community service activity aims to improve students' understanding of Islamic accounting literacy through socialization of new issues in Islamic accounting. Held on June 5-10, 2024 at the University of West Sulawesi, this activity includes administrative and technical preparation, implementation of socialization, and preparation of activity results reports. This activity succeeded in increasing participants' knowledge of Islamic accounting and received an enthusiastic response from students. It is expected that this activity will strengthen students' understanding and prepare them to contribute to the development and implementation of sharia accounting, as well as support the growth of sharia economy in Indonesia. Synergy between various parties, including academics, scholars, financial services authorities, and sharia financial institutions, is very important to achieve the ideal goals of sharia economy. Keywords: Socialization; Innovation; Sharia Accounting. Abstract: Islam mengajarkan prinsip-prinsip komprehensif dan menyeluruh yang mencakup seluruh aspek kehidupan manusia, termasuk dalam bidang ekonomi. Salah satu aspek penting dalam ekonomi syariah adalah akuntansi syariah, yang bertujuan mengintegrasikan prinsip-prinsip syariah dalam sistem akuntansi modern untuk menciptakan sistem yang lebih adil dan bermartabat. Dengan pertumbuhan pesat pasar keuangan dan kebutuhan literasi keuangan yang semakin mendesak, pemahaman tentang akuntansi syariah menjadi krusial. Penelitian ini mengidentifikasi bahwa literasi keuangan syariah di masyarakat Riau, khususnya di Kota Pekanbaru dan Kuantan Singingi, masih rendah, sehingga edukasi tentang keuangan syariah sangat diperlukan.  Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pemahaman mahasiswa tentang literasi akuntansi syariah melalui sosialisasi isu-isu kebaharuan akuntansi syariah. Dilaksanakan pada 5-10 Juni 2024 di Universitas Sulawesi Barat, kegiatan ini mencakup persiapan administrasi dan teknis, pelaksanaan sosialisasi, serta penyusunan laporan hasil kegiatan. Kegiatan ini berhasil meningkatkan pengetahuan peserta mengenai akuntansi syariah dan mendapatkan respons antusias dari mahasiswa. Diharapkan kegiatan ini akan memperkuat pemahaman mahasiswa dan mempersiapkan mereka untuk berkontribusi dalam pengembangan dan penerapan akuntansi syariah, serta mendukung pertumbuhan ekonomi syariah di Indonesia. Sinergi antara berbagai pihak, termasuk akademisi, ulama, otoritas jasa keuangan, dan lembaga keuangan syariah, sangat penting untuk mencapai tujuan ideal ekonomi syariah.